2019
DOI: 10.35207/later.639337
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension and Vocabulary Size of CLIL and Non-CLIL Students: A Comparative Study

Abstract: Content and Language Integrated Learning (CLIL) has a dual focus both on content and language teaching in which students learn through and about language and provides contextualized and meaningful situations. Although studies on the impact of CLIL on learners' vocabulary knowledge and reading comprehension have mostly positive results, related research is highly limited in Turkish context. Thus, this study aims to examine to what extent CLIL students differ from non-CLIL students in terms of their reading comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…The result depicted in both tables was consistent and harmonious with empirical research works conducted by different scholars who came up with the ndings that CLIL approach signi cantly fostered reading comprehension (e.g. see Bayram et al, 2019;Binsaran, 2021;Hamidavi et al, 2016;Yang, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…The result depicted in both tables was consistent and harmonious with empirical research works conducted by different scholars who came up with the ndings that CLIL approach signi cantly fostered reading comprehension (e.g. see Bayram et al, 2019;Binsaran, 2021;Hamidavi et al, 2016;Yang, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Studies have also explored the ways in which language learners’ reading skills and lexical knowledge can be developed (e.g., Aktan-Erciyes, 2020; Altay, 2017; Bayram et al, 2019; Er Doğan & Mede, 2016; Nişancı, 2017; Öztürk & Şenaydın, 2019). For instance, Bayram et al (2019) found advantages of content and language integrated language learning (CLIL) over non-CLIL contexts in terms of improving learners’ reading comprehension as well as receptive and productive vocabulary knowledge. Nişancı (2017) illustrated the role of extensive reading in promoting high school EFL learners’ implicit phonological knowledge and improving their word recognition fluency at large.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%
“…EMI-CLIL research has employed different types of language tests to measure language learning outcomes. Some studies have adopted validated tests like the standardized Key English Test (Cambridge ESOL, 2008), employed by Merino and Lasagabaster (2018), and the Vocabulary Levels Test developed by Schmitt et al (2001), which has been widely employed in EMI-CLIL research targeting vocabulary developments (e.g., Bayram et al, 2019;Castellano-Risco et al, 2020). Other studies have employed self-designed tests, conveniently and purposefully developed by the researchers, sometimes in collaboration with the teachers in the target context.…”
Section: Language Test Typementioning
confidence: 99%